Analysis of a Vertical Cavity Surface Emitting Laser Excited by a Rectangular Pulse - Eladl, Sh.M.; Nasr, A.; Sharaf, A. (Journal of semiconductor technology and science, 2022)
In this paper, a theoretical analysis of a Vertical Cavity Surface Emitting Laser (VCSEL) excited by a rectangular pulse signal is developed. The analytical model is based on the transfer function of the laser characteristic equation. The transient behavior of the device under investigation at different widths of input rectangular pulse signals is studied, the output derivative of the optical output power as a measure of the device speed is also analyzed. All interesting parameters are taken into account. In addition, the effect of the width of the input pulse signal and the resonance frequency are also considered. The results show that higher resonant frequency makes the device to arrive to a saturated definite value very faster than the lower resonant frequency. Also, the increased resonance frequency makes the device to change its case from high current state to low current state faster than the lower resonant frequency. This type of device reached the steady state at very short time; it can be exploited in different applications of very high speed optical systems. KCI Citation Count: 0